Maternal and neonatal hyponatremia during labor: a case series. (18th August 2019) - Solomon, Neta; Many, Ariel; Orbach, Rotem; Mandel, Dror; Shinar, Shiri
Abstract: Background: Hyponatremia during labor and delivery may result in severe maternal and neonatal sequelae. Our aim was to describe the direct effect of hyponatremia in labor on pregnancy outcome. Methods: A case series of parturients diagnosed with hyponatremia during labor and their neonates. Clinical presentation, laboratory workup, and maternal and neonatal outcomes are presented. Results: Four parturients and their corresponding six neonates were diagnosed with hyponatremia. Of these, two cases were caused by water intoxication and two were preeclampsia induced. While two were identified due to maternal or neonatal symptoms, two were diagnosed by routine laboratory testing. In all cases, low maternal sodium resulted in similarly low neonatal sodium. Neonatal symptoms included respiratory distress syndrome (RDS), lethargy, and jaundice. Conclusion: Psychogenic drinking during labor and preeclampsia may predispose to maternal hyponatremia, resulting in neonatal hyponatremia. Early recognition and treatment can prevent further maternal deterioration and adverse neonatal sequelae.